Diversity of knowledge in patent co-authorship networks – case studies in the Victorian biotechnology industry. Issue 4 (4th November 2014) - Moslehi, Adel; Linger, Henry; Tanner, Kerry
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to understand the role of k-networks in knowledge creation, as existing literature argues that network structure does not provide sufficient explanation per se. This paper proposed diversity as an important construct to explain knowledge creation in SMEs' k-networks. Design/methodology/approach – First, by reviewing the literature, this paper proposes a hypothesis that predicts a positive association of content and knowledge creation. Then, focusing on patent co-authorship networks of the biotechnology industry in Victoria, this research used an explanatory multiple case study approach to test the formulated hypothesis. Findings – By introducing new constructs, the results provide more insight on the positive association of knowledge content and knowledge creation. Based on the emergent constructs, rival hypotheses are also developed for further research. Originality/value – Beyond the role of network structure, which has dominated the knowledge network literature, this research highlights how other factors like knowledge diversity are needed to be consider.